The PENGARUH MODEL PJOJECT BASED LEARNING (PJBL) TERHADAP KETERAMPILAN MENULIS TEKS BERITA DI SMPN 36 KOTA PADANG - Reska Syofyani Putri; Farel Olva Zuve (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe students' news text writing skills before and after using the Project-Based Learning (PjBL) model, as well as to analyze the influence of the model on these skills. This is a quantitative study. The population comprised all Grade VII students at SMP Negeri 36 Padang, totaling 134 students, with Class VII.2 selected as the sample through purposive sampling. The research instrument was a performance test evaluating news text writing skills. The results indicated that students' news text writing skills before the treatment were in the Almost Sufficient category, with an average score of 54.98. Following the treatment, performance improved to the Good category, with an average score of 79.40. Hypothesis testing revealed a significant effect of the Project-Based Learning model on students' news text writing skills. Therefore, this learning model is effective in improving students' news text writing skills and optimizing their mastery of the text's structure and linguistic features.